Multivalued Impulsive SDEs Driven by G-Brownian Noise: Periodic Averaging Result. (14th December 2022) - Abouagwa, Mahmoud; Khalaf, Anas D.; Gul, Nadia; Alyobi, Sultan; Mohamed, Al-Sharef
Abstract : This paper aims to study two approximation theorems in view of the periodic averaging results for non-Lipschitz multivalued stochastic differential equations with impulses and G-Brownian motion (MISDEGs). By adopting G-Itô's formula and non-Lipschitz condition, the solutions to the simplified MSDEGs without impulses may replace those of the initial MISDEGs in view of approximation in L 2 -sense and capacity. Finally, we bring a couple of two examples to enhance our theoretical results.